Analysis of the Strategy for Collecting Zakat, Infaq and Sadaqah (ZIS) Funds at the LAZISMU UMY Zakat Institution in Yogyakarta - Sutrisno, Sutrisno (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the fundraising strategies for Zakat, Infaq, and Sadaqah (ZIS) at the zakat institution of the oldest private Islamic university in Yogyakarta. The research seeks to identify the effectiveness of fundraising methods employed and analyze the supporting and inhibiting factors in the fund management of the zakat institution, specifically at Lazis LAZISMU UMY. This study adopts a descriptive qualitative approach, utilizing data collection techniques such as interviews, observations, and documentation. The data analysis technique involves data reduction, data presentation, and conclusion drawing. The findings indicate that the institution employs direct fundraising methods, including, face-to-face meetings, salary deductions, donation boxes, digital fundraising, fundraising during events, and door-to-door donation collection. Additionally, indirect fundraising is conducted through; education and awareness programs, strategic partnerships, volunteer activities, sustainable programs, and reward programs. The effectiveness of fundraising through face-to-face interactions and digital platforms is primarily influenced by personal engagement with donors and educational awareness. Supporting factors include the involvement of the academic community, volunteers, and institutional collaborations. In contrast, challenges include competition among zakat institutions, limitations in amil certification and human resources, suboptimal operational management, and insufficient education and facilities. The fundraising strategies play a crucial role in ZIS fund management, contributing positively to fund growth and community benefits. However, the main challenge faced is the inability to fully achieve the targeted fundraising goals.